KAJIAN PEMBELAJARAN MENGGUNAKAN MODEL SCRAMBLE TERHADAP HASIL BELAJAR DI SEKOLAH DASAR - Kharisna, Feby; Firman, Firman; Desyandri, Desyandri (Study program PGSD FKIP Universitas Bung Hatta, 2022)
This research uses an approach approach, literature study. The purpose of this study was to analyze the improvement of learning outcomes through the use of scrambled models of elementary school student learning outcomes. The researcher collected data from this study by collecting and reviewing consistent data from previous researchers. The result of this study is an increase in learning outcomes of elementary school students who use the scrambled model. Students during the learning process using the scramble model are asked to answer several questions where the letters are encrypted and the words are encrypted. This learning model is very useful and not boring for elementary school students.